COMPARATIVE ANALYSIS OF SUSTAINABILITY REPORTING QUALITY ON GRI STANDARDS - Triwacananingrum, Wijaya; Azaria, Andrea; Elizabeth, Elizabeth; Novia, Giovani (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2024)
The performance and success of a company is not only seen from a financial perspective, but also how the company can survive and manage resources sustainably. Therefore, companies need awareness of the importance of preparing sustainability reports as a basis for assessing company performance in non-financial terms. Guidelines for creating sustainability reports were prepared by the Global Reporting Initiative, which recently revised previous guidelines. This change in guidelines has only been implemented in the last two years, so further research is needed regarding its impact on the quality of sustainability reports. The data collection technique is carried out by analyzing the relevant documents, namely the company's sustainability report. Reports are analyzed based on predetermined indicators, and then classified in interval form so that they can be ranked based on the assessment compiled by NCSR in the ASRR assessment. It can be concluded from the research results that there were 107 changes in disclosure, which we then grouped into 11 sectors; the impact of changes in guidelines was most felt by the financial service company sector. Then the calculation results also show a change in the quality of sustainability reports from changing the GRI-G4 guidelines to GRI-Standards. These changes resulted in an increase in the report's quality rating from "Poor" to "Fair". This shows that the change in sustainability reporting guidelines from GRI-G4 to GRI-Standards has had a positive impact on the quality of sustainability reports. Changes in quality are progressive, so it is believed that the results obtained can improve if the research is carried out again in the next few years.